Parenting gifted and talented children: challenges parents have and their role in children’s academic performance - Baimukanova, Raikhan (Nazarbayev University Graduate School of Education, 2020)
The challenge of parenting gifted and talented children is becoming more and more relevant in Kazakhstan. It is well – known that gifted and talented children have specific educational needs that have to be identified and supported in a school system, and there are some obstacles in terms of parenting. The parents of gifted and talented children require assistance not only with providing their children with conditions to meet their educational needs but also with the issues of parenting such children. The aim of this research study is to explore parenting gifted and talented children in a selected Nazarbayev Intellectual school in Kazakhstan. This study also investigates the role of parents in children’s academic performance, and challenges parents face in rearing gifted and talented students. The purpose of the present study is to identify the challenges parents face and determine their roles in their talented and gifted children’s academic performance. The central research questions are as follows: a) What are the main challenges parents face supporting their gifted and talented children academically? b) What is the role of parents in their talented and gifted child’s academic performance? A total of seven face-to-face semi-structured interviews were conducted. The findings revealed that parents held two views, and that distinguish, among others. First, some parents believe that each child is gifted, whereas others think giftedness is an ability that can be identified and developed at a certain period of time. Second, parents are aware that gifted children are a very heterogeneous group of children and that they have diverse characteristics and needs that need to be addressed. Based on the results of this study, I have concluded that parents are lacking support and help in rearing their gifted children. Another finding is that parenting talented children in a Kazakhstani context needs further studies to promote inclusive practices in rearing such children.
Keywords: parenting, gifted and talented children, academic performance